235k views
2 votes
Helppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppp

Helppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppp-example-1
User Bassirou
by
4.8k points

2 Answers

3 votes

Answer:

C. 11

Explanation:

f(x)=-5x+1

f(-2)=-5(-2)+1

f(-2)=10+1

f(-2)=11

User ILovemyPoncho
by
6.0k points
3 votes

Answer: 11 is correct

Explanation:

As attached

Helppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppppp-example-1
User Tim Koelkebeck
by
5.4k points